Analysis Of the Application Method Of the Ancak Giring System On Mineral Land and Oil Palm Peat Land PT. PP. London Sumatra Tbk. Tanjung Makmur Plantation Division 02 And Division 03 - Widya Ayu Eka Purbaningsih; Puspita; Andi Lelanovita Sardianti; Sri Ngapiyatun; Sukariyan (JURNAL AGRIMENT, 2025)
The purpose of this study wass to determine or analyze the harvest production in the oil palm fruit ancak giring system on mineral land and peat land and to determine the quality of oil palm harvest results in mineral land and peat land conditions at PT. PP. London Sumatra Indonesia Tbk., Tanjung Makmur Estate Plantation Division 02 and Division 03. The study was conducted at PT. PP. London Sumatra Indonesia Tbk., Tanjung Makmur Plantation, Gunung Bayan Village, West Kutai, East Kalimantan, on 2-30 September 2024. The method used was qualitative with a purposive sampling techique. Data were obtained from 12 informants through interviews, field observations, and document collection. The results showed that harvest productivity on peat land was higher than on mine land. However, the quality of the harvest, both in terms of ancak conditions and fruit ripeness, tended to be better on mineral land. On mineral land (Division 2) production reached 17,161 bunches in two months, and on peat land (Division 3) it reacher 19,533 bunches. In August: Division 2 harvested 6,881 bunches (11 bunches of unripe fruit, because of long fronds). Division 3 harvested 7,436 bunches (13 bunches of unripe fruit, because of thick weeds). Meanwhile, in September: Division 2 increased to 110,280 bunches (13 bunches of unripe fruit, because it had not been pruned), and Division 3 harvested 12,097 bunches without unripe fruit.